Flexible High‐Resolution Triboelectric Sensor Array Based on Patterned Laser‐Induced Graphene for Self‐Powered Real‐Time Tactile Sensing. (29th March 2021) - Yan, Zhengguang; Wang, Liangliang; Xia, Yifan; Qiu, Rendong; Liu, Wenquan; Wu, Min; Zhu, Yan; Zhu, Shunli; Jia, Chunyang; Zhu, Miaomiao; Cao, Ruirui; Li, Zhaoling; et al.
Abstract: Flexible tactile sensors are garnering substantial interest for various promising applications, including artificial intelligence, prosthetics, healthcare monitoring, and human–machine interactions (HMI). However, it still remains a critical challenge in developing high‐resolution tactile sensors without involving high‐cost and complicated manufacturing processes. Herein, a flexible high‐resolution triboelectric sensing array (TSA) for self‐powered real‐time tactile sensing is developed through a facile, mask‐free, high‐efficient, and environmentally friendly laser direct writing technique. A 16 × 16 pixelated TSA with a resolution of 8 dpi based on patterned laser‐induced graphene (LIG) electrodes (7 Ω sq −1 ) is fabricated by the complementary intersection overlapping between upper and lower aligned semicircular electrode arrays. With the especially patterning design, the complexity of TSA and the number of data channels is reduced. Meanwhile, the TSA platform exhibits excellent durability and synchronicity and enables the achievement of real‐time visualization of multipoint touch, sliding, and tracking motion trajectory without power consumption. Furthermore, a smart wireless controlled HMI system, composed of a 9‐digital arrayed touch panel based on a LIG‐patterned triboelectric nanogenerator, is constructed to control personal electronics wirelessly. Consequently, the self‐powered TSA as a promising platform demonstrates great potential for an active real‐time tactile sensing system, wireless controlled HMI, security identification and, many others. Abstract : A flexible high‐resolution triboelectric sensing array (TSA) based on patterned laser‐induced graphene (LIG) is developed for self‐powered real‐time tactile sensing. The 16 × 16 pixelated TSA (8 dpi) is fabricated to achieve real‐time visualization of multipoint touch, sliding, and tracking motion trajectory. Moreover, a smart wireless controlled human–machine interface system based on LIG‐patterned triboelectric nanogenerator is constructed to control personal electronics wirelessly.